On the Linguistically Responsive Teacher in Tertiary Education (Linguist, 2021)
This article contributes to the debate among applied linguists regarding the importance of teachers’ linguistic awareness (TLA) in the teaching of foreign languages. While this debate relates to teaching practices in the pre-university stage, this article focuses on linguistic awareness in tertiary education, more specifically in English departments in Morocco. The article starts with outlining the various dimensions of this concept with references to the major levels of linguistic analysis (phonology, morphology, syntax and pragmatics). Then it deals with three basic questions: what is being done? What could be done? And what should be done? for TLA to be adopted in the teaching of English in Morocco. To support the arguments put forward here, 24 university teachers were interviewed to obtain information relating to their linguistic awareness as well as the ways TLA is exploited in their classrooms. 16.66% of the subjects showed strong TLA and stated that they strive to exploit it individually in their teaching. 29.16% have a good working background in linguistics, but they do not know how to exploit it in their classrooms. More importantly, 54.16% of the informants do not feel that they have such background and tend to teach English without any reference to knowledge about language. The article concludes that Moroccan teachers of English are called to develop and exploit TLA with a view to achieving better learning outcomes, in line with proposals provided herein to redress this situation in Morocco.
Keywords: Teachers’ linguistic awareness; foreign languages; levels of linguistic analysis; teaching; tertiary education